2022
DOI: 10.1039/d1na00783a
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of electrical properties in MoTe2by XeF2-mediated surface oxidation

Abstract: Transition metal dichalcogenides (TMDs) are promising candidates for semiconductor industry owing to their superior electrical properties. Their surface oxidation is of interest because their electrical properties can be easily modulated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…The XeF 2 exposure is a widely used technique to etch MoS 2 layers efficiently. [ 66 ] Thus, the complete protection of MoS 2 by the graphene layer further confirms that the fluorination under XeF 2 exposure is unidirectional. The difference between the observed results with the observation of Son et al.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The XeF 2 exposure is a widely used technique to etch MoS 2 layers efficiently. [ 66 ] Thus, the complete protection of MoS 2 by the graphene layer further confirms that the fluorination under XeF 2 exposure is unidirectional. The difference between the observed results with the observation of Son et al.…”
Section: Resultsmentioning
confidence: 68%
“…The XeF 2 exposure is a widely used technique to etch MoS 2 layers efficiently. [66] Thus, the complete protection of MoS 2 by the graphene layer further confirms that the fluorination under XeF 2 exposure is unidirectional. The difference between the observed results with the observation of Son et al [31] is due to the fact that we have used very high quality ultra-flat SiO 2 /Si surface which shows roughness <0.3 nm (Figure S25, Supporting Information).…”
Section: Unidirectional Fluorinationmentioning
confidence: 62%
“…While most studies used O 2 plasma to oxidize the TMD surface for FET devices, Ji et al used XeF 2 plasma etching for oxidation of MoTe 2 . They showed that since MoTe 2 is prone to oxidation in air, keeping MoTe 2 in air after plasma etching resulted in oxidation due to defects created during plasma treatment.…”
Section: Oxidationmentioning
confidence: 99%
“…556 Oxidation of MoS 2 channels in MoS 2 -based transistors by UV/ O 3 can also enable memristive switching characteristics with potential usage as memtransistors for energy-efficient neuromorphic electronics. 557 While most studies used O 2 plasma to oxidize the TMD surface for FET devices, Ji et al 558 used XeF 2 plasma etching for oxidation of MoTe 2 . They showed that since MoTe 2 is prone to oxidation in air, keeping MoTe 2 in air after plasma etching resulted in oxidation due to defects created during plasma treatment.…”
Section: Fet and Electronic Devicesmentioning
confidence: 99%